Effect of Novobiocin and Its Combination with Tetracycline, Chloramphenicol, Erythromycin, and Lincomycin on the Microbial Generation of Escherichia coli - Garrett, Edward R. (1973)
Inhibition of the steady-state generation of Escherichia coli by the bacteriostatic antibiotic novobiocin is linearly related to drug concentration in the range of 0 to 30 μg/ml. Increased cell sizes result because the drug inhibits cell division. The generation rate dependence on drug concentration depends on the nonionized fraction of novobiocin and is invariant with inoculum size or medium composition. However, the antibacterial activity of novobiocin decreases as the concentration of nutrients and Mg(2+) increases, although the inhibitory action of novobiocin on generation rate remains unchanged for concentrations of Mg(2+) above 8.1 × 10(−4) M. Novobiocin is synergistic in combinations with tetracycline in broth, but not when the Mg(2+) was maintained at 4.05 × 10(−3) M. Combinations of novobiocin with the 50S ribosomal subunit inhibitors chloramphenicol, erythromycin, or lincomycin are antagonistic, and the degree of growth inhibition is determined only by that component of the binary combination that would have the greater potency if it were acting alone.